Evaluation of adherence and anti-infective properties of probiotic Lactobacillus fermentum strain 4-17 against Escherichia coli causing urinary tract infection in humans. (June 2019) - Falah, Fereshteh; Vasiee, Alireza; Behbahani, Behrooz Alizadeh; Yazdi, Farideh Tabatabaee; Moradi, Samira; Mortazavi, Seyed Ali; Roshanak, Sahar
Abstract: Gastrointestinal (GI) infection is one of the most common types of infectious diseases. Application of probiotic strains in the control of such infections represents a promising approach. In this study, Lactobacillus fermentum strain 4-17 was isolated from kashkineh, an Iranian cereal fermented food, and identified by sequencing its 16S rRNA gene using universal primers. Its probiotic features, including resistance to acid, bile tolerance, antibacterial activity, resistance to intestinal and gastric juices, and hydrophobicity were evaluated. The ability of this strain to adhere to human intestinal cells as well as the anti-adhesive effect of L. fermentum strain 4-17 against E. coli isolated from patients with urinary tract infection was investigated. L. fermentum strain 4-17 was capable of surviving at various conditions such as low pH values, bile salts exposure, and GI tract environment. It showed 43% cell hydrophobicity. The adhesion level of L. fermentum strain 4-17 to human colon adenocarcinoma Caco-2 cells was 8.5% which was also confirmed by scanning electron microscopy (SEM). Furthermore, this strain showed appropriate anti-adhesive properties (including competition, inhibition and replacement properties) against human pathogenic bacteria. These data suggest that L. fermentum strain 4-17 could be examined further for its useful effects and introduced as a novel candidate probiotic to control GI infection disease. Highlights: We assessed probiotic properties of Lactobacillus fermentum strain 4-17. Our strain showed good adaptation to gastrointestinal conditions. The anti-infective effect of Lactobacillus fermentum strain 4-17 against Escherichia coli was acceptable.